PENGARUH PEMBERIAN KCl DAN SISTEM TUMPANG SARI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata S.) - Eva Sri Artina; Ahmad Nadhira; Dedi Kurniawan (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2023)
Introduction: The purpose of this study was to determine the effect of intercropping system of kcl fertilizer on the growth and production of sweet corn plants. Research Method: This research was conducted in Pasar VIII Namo Terasi Village, Sei Bingai District, from October 2022 - January 2023. The study used a Factorial Randomized Block Design (RBD) with 2 treatment factors. The first factor KCl consisted of treatment levels, namely K0 = 0 g/plant, K1 = 10 g/plant, K2 = 15 g/plant. The second factor was intercropping with three treatment levels of peanut spacing, namely T1 = 20 x 15 cm, T2 = 20 x 20 cm, T3 = 20 x 25 cm. Parameters observed were Plant Height (cm), Plant Cob Weight (gr). Cob Weight Per Plot (kg), and Number of Fruits Per Plot (fruit). Results: The results showed that the kcl treatment had no significant effect on all parameters. The best treatment for kcl was K1 (10 grams), the best treatment for the intercropping system was T2 (20x20), and the best treatment for the interaction between the two treatments was K1T2. Keywords: Sweet corn, KCl Fertilizer, and Peanut Intercropping.